Haemagglutination (HA) test of Helicobacter pylori (Baghdad Science Journal, 2014)
Thirty clinical isolates of Helicobacter pylori bacteria obtained from patients attending endoscopy unit of Ibn-Sena teaching hospital in Mosul . These patients were complaining from epigastric pain , dyspepsia , acidity , vomiting , abdominal pain , flatulance , heart burn and melena . The H. pylori isolates were used for Haemagglutination assay (HA) , which involves the recognition of various glycoconjugates on the surface of red blood cells . In this study sheep red blood cells has been used in (HA) assay because the sheep erythrocytes surface resemble that of human epithelial cells .The results proved by (HA) assay, the ability of H. pylori to adherence to specific receptors on the surface of Human Epithelial Cell , which is the first step in the pathogenic process .